Auditory ossicles: a potential biomarker for maternal and infant health in utero - Tamara Leskovar; Julia Beaumont; Nidia Lisić; Suzanne McGalliard (Taylor & Francis Group, 2019)
Background: Carbon (δ13C) and nitrogen (δ15N) isotope ratios of collagen from teeth and bone are used to study human nutrition and health. As bones are constantly remodelling throughout life, isotopic values of bone collagen represent an average of several years. In contrast, human teeth do not remodel and their primary dentine contains only the isotopic data from the time of formation. In contrast to all other bones, human auditory ossicles also appear not to remodel. As they develop in utero and finish formation in the first 2 years of life, their collagen should also represent isotopic values of these two relatively short periods. Aim: By comparing δ13C and δ15N data from ossicles and incremental dentine, this study aims to investigate how two developmental periods of the ossicles, in utero and the first 2 years of life, reflect in collagen obtained from the ossicles. Subject and methods: Ossicle and tooth samples of 12 individuals aged 0.5 ± 0.4 years to 13 ± 1 years from the nineteenth century St. Peter's burial ground in Blackburn were collected and processed to obtain bulk bone and incremental dentine collagen which was measured for δ13C and δ15N. Results: Averaged δ13C and δ15N of ossicles are lower when compared to every age group except after 3 years of age. Average offset between ossicles and dentine of different groups ranges from 0.4-0.9‰ for δ13C and from 0.3-0.9‰ for δ15N, with highest counterbalance at birth and after the first 5 months after birth. Conclusions: There appears to be a systematic offset between the dentine and ossicle data. It seems that the second phase of development does not influence the isotopic values of collagen significantly and the data we are obtaining from ossicles represents the in utero period.